Un laboratorio de complicidad creativa. - Labeur, Paula (Enunciación)
This paper reflects on an experience of teacher education in language and literature during teacher residency classes. During these sessions, students carry out their teaching practice in secondary schools with upon the basis of writing fiction as a way to teach literature. This practice is revealed through the production of conjectural scripts with which the resident teachers organize their classes, within a framework of collaborative discussion about the implementation of writing workshops, as well as their later reflections on what happened in them. An analysis of the texts produced by the resident teachers shows the secondary school students' appropriation regarding the employed concepts of literature and those of the residents with regard to the methodology they implement as teachers. If writing conjectural scripts as texts of anticipation is to invent the ways in which a certain classroom scene would unfold, recording the subsequent practice allows not only analyzing the ways to appropriate disciplinary knowledge in the classroom, but also building knowledge about the practice, a self-referential knowledge about the training experience itself within the framework of the practice in which residents become teachers.